An Empirical Study of Impact of Demography on Online Reservation in a Selected City in India - Sharan, J; Renugadevi, S (Journal of Advanced Research in Entrepreneurship, Innovation and SME Management, 2022)
An online reservation system simply refers to booking of tickets or reserving of a space or seats through the internet. This study enquires into impact of demographic factors on online reservation which includes train, bus, and flight. This study followed an empirical method and it was undertaken during the years 2015 to 2016. Sample size was 100 and convenient sampling technique was used. Data was collected using a pre-tested questionnaire from the consumers in Madurai city, TN, India. The study concluded that education, income, or age have no impact on online reservation. However, to some extent, gender plays a role in consumer attitude towards online reservations. How to cite this article: Renugadevi S, Sharan J. An Empirical Study of Impact of Demography on Online Reservation in a Selected City in India. J Adv Res Entrep Innov SMES Mgmt 2021; 4(2): 1-5.